Réponses

Meilleure réponse !
2013-05-23T17:52:29+02:00

Il faut développer et réduire :

 

3(x - 6) = 18  

3x - 18 = 18

3x - 18 + 18 = 18 + 18

3x = 36

3x / 3 = 36/3

x = 12

 

4 + (2 - y) = 20  

4 + 2 - y = 20

6 - y = 20

6 - y - 6 = 20 - 6

- y = 14

y = -14

 

-5(2x + 3) = 25

-10x - 15 = 25

-10x - 15 + 15 = 25 + 15

-10x / -10 = 40/ -10

x = -4

 

1 - 3(2x + 4) = -22

1 - 6x - 12 = - 22

-6x - 11 = -22

-6x - 11 + 11 = -22 - 11

-6x / -6 = -33/-6

x = 33/6

 

2013-05-23T17:55:19+02:00
A) 3(x-6)=18
3x-18=18
3x=18+18
x=12

b)4+(2-y)=20
2-y=20-4
-y=16/2
y=-8

c)-5(2x+3)=25
-10x-15=25
-10x=25+15
x=40/-10
x=-4


d)1-3(2x+4)=-22
-6x-12=-22-1
-6x=-23+12
x=11/6